Development of students’ vocational competence in the frame of extracurricular activities - Kolchenko, Kateryna; Kozlikovska, Nadiia (Social Welfare: Interdisciplinary Approach, 2012)
One of the most important conditions of future specialist’s vocational competence is a well-balanced combination of learning, scientific research and practice, which is not easy to achieve in terms of traditional education. Extracurricular activity in the form of educational-scientific-production student units (ESPSU) favours both active and creative learning of theory and practical skills formation vital for students’ further vocational activity. Six-year experience of extracurricular activities in Open International University of Human Development “Ukraine” shows ESPSU participants’ positive results comparing to other students in their academic achievements, professionalism and career development.